Validitas dan praktikalitas LKPD berbasis model simas eric pada materi pengukuran dan vektor untuk kelas X SMA/MA - Puja Asni Wahyu; Amali Putra; Hamdi Hamdi; Fatni Mufit (Universitas Negeri Padang, 2019)
This research is motivated by the facts in the field that students' understanding was low because students are not actively involved in learning. Learning activities of students can be optimized by the use of conducive equipment of learning. Equipment of learning is suitable to describe the active involvement of students in learning is student worksheet. The purpose of this research is to produce a student worksheet based on simas eric models on the content of measurement and vector that is suitable for physics learning in class X SMA / MA from the aspects of validity and practicality. The type of research applied is R&D (Research and Development) using 3 stages out of 4 4-D stages developed by Thiagarajan, et al. those are define, design, and development. Subject of the research are 33 students class XII from SMAN 3 Padang Panjang, 2 teachers Physics from SMAN 3 Padang Panjang, 4 Physics lectures from FMIPA UNP and a learning model developer. Validation of product are reviewed from two aspects those are the feasebility of equipment of learning and simas eric learning model. The analysis technique used in this research is quantitative analysing using formula momen kappa. The result of validaty of the feasebility of equipment of learning was 0,83 with very valid criteria and validaty of simas eric learning model was very valid with value 0,85. The result of practicality by the teacher was 0,81 with very practical criteria and practicality by students was practical criteria with value 0,79.